Kinetics of Ganglioside-Rich Supported Lipid Bilayer Formation with Tracer Vesicle Fluorescence Imaging - Sharma, Anurag (Langmuir : the ACS journal of surfaces and colloids, 2023)
Gangliosides, forming a class of lipids complemented by sugar chains, influence the lateral distribution of membrane proteins or membrane-binding proteins, act as receptors for viruses and bacterial toxins, and mediate several types of cellular signaling. Gangliosides incorporated into supported lipid bilayers (SLBs) have been widely applied as a model system to examine these biological processes. In this work, we explored how ganglioside composition affects the kinetics of SLB formation using the vesicle rupturing method on a solid surface. We imaged the attachment of vesicles and the subsequent SLB formation using the time-lapse total internal reflection fluorescence microscopy technique. In the early phase, the ganglioside type and concentration influence the adsorption kinetics of vesicles and their residence/lifetime on the surface before rupturing. Our data confirm that a simultaneous rupturing of neighboring surface-adsorbed vesicles forms microscopic lipid patches on the surface and it is triggered by a critical coverage of the vesicles independent of their composition. In the SLB growth phase, lipid patches merge, forming a continuous SLB. The propagation of patch edges catalyzes the process and depends on the ganglioside type. Our pH-dependent experiments confirm that the polar/charged head groups of the gangliosides have a critical role in these steps and phases of SLB formation kinetics